"We Weren't Prepared for This": Parents' Experiences of Information and Support Following the Premature Birth of Their Infant. Issue 3 (July 2019) - Blackburn, Carolyn; Harvey, Merryl
Abstract : Having a child born prematurely can plunge parents into an unknown and sometimes frightening situation, where they experience a loss of control over events and reduced decision-making capacity. Preterm birth sometimes results in posttraumatic stress disorder for parents and negatively impacts on parent–child interactional patterns, especially if parents were unprepared for this eventuality. The role of information, support, and early intervention in parents' coping capacity in this situation has been noted in developmental systems theory to contribute to family interactional patterns. This article reports on a mixed-methods study that explored the information and support needed by and available to parents following preterm birth in England and the effect of this on their emotional well-being. The findings suggest that support systems do not always provide timely or helpful emotional or practical support to parents, and this has the potential to place additional stress on family interactional patterns, especially where parents were unprepared for the possibility of preterm birth.